2017
DOI: 10.2147/jpr.s135037
|View full text |Cite
|
Sign up to set email alerts
|

Success with neurotropin in treating pediatric lower extremity pain induced by spinal cord injury after epidural anesthesia

Abstract: Spinal cord injury (SCI) complicated by epidural anesthesia, though rare, can result in neuropathic pain. However, the treatment for this kind of life-altering injury remains a challenge. A 7-year-old girl was referred with dyskinesia and severe pain in her right lower extremity due to an accidental SCI following lumbar puncture. After treatment with analgesics such as gabapentin, mecobalamin, and dexamethasone/methylprednisolone for 1 week, the myodynamia had improved, but progressive pain persisted. After tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The drug NTP is a kind of multicomponent biological agent while NM is a chemical agent, which determines their own unique functions on microenvironment in SCI treatment. A non-protein extract isolated from inflamed rabbit skin inoculated with vaccinia virus, NTP is used to treat intractable neuropathic pain in clinical work (27,28). Analysis of its components showed that NTP was composed of more than 300 small molecular compounds and some of them have been showed neurotrophic effect, such as GABA, carnosine and adenosine.…”
Section: Discussionmentioning
confidence: 99%
“…The drug NTP is a kind of multicomponent biological agent while NM is a chemical agent, which determines their own unique functions on microenvironment in SCI treatment. A non-protein extract isolated from inflamed rabbit skin inoculated with vaccinia virus, NTP is used to treat intractable neuropathic pain in clinical work (27,28). Analysis of its components showed that NTP was composed of more than 300 small molecular compounds and some of them have been showed neurotrophic effect, such as GABA, carnosine and adenosine.…”
Section: Discussionmentioning
confidence: 99%
“…As NTP is prescribed to alleviate chronic pain—it activates the descending pain suppression system by enhancing noradrenergic receptors and serotonergic systems [ 6 ]—whether the drug could be used to alleviate neuropathic pain after injury warrants research. One report documented the case of a 7-year-old girl with SCI whose condition was complicated by epidural anaesthesia [ 34 ]. Moreover, NTP also reportedly features potential as an antidepressant [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…NTP has been widely used in Japan and China for more than 50 years as an analgesic for chronic skeletal muscle and neuropathic pain. [7][8][9] NTP contains various bioactive molecules, including nucleic acids, amino acids, and sugars. [10] Although the biologically active components responsible for its beneficial effects have not been identified, NTP exerts analgesic effects through the activation of the descending pain inhibitory system and induction of brain-derived neurotrophic factor.…”
Section: Introductionmentioning
confidence: 99%